STUDI LITERATUR: PENGARUH PENDIDIKAN KEWARGANEGARAAN - Arifin Lubis, Juliana Dwi; Ndona, Yacobus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Citizenship education functions to form citizens who are intelligent, responsible and able to play an active role in social and democratic life. This education plays an important role in facing global challenges by instilling national, moral and democratic values ​​through three educational centers: home, school and community. Therefore, citizenship education is considered as a solution to prepare the younger generation to think critically and build national awareness based on the values ​​of Pancasila. The method used is a literature study which examines various sources related to literature studies. The influence of Civic Education on students' social awareness is based on literature study research where the author collects data and information in the form of relevant journals, documents, dialogue books, magazines, articles, etc. other.